Motivating factors and barriers to help-seeking for casino gamblers: results from a survey in Swiss casinos - Lischer, Suzanne; Schwarz, Jürg; Wallimann, Hannes; Jeannot, Emilien; Mathys, Jacqueline (Frontiers in Psychiatry, 2023)
Introduction Gambling can have serious consequences for many aspects of a person’s life. Yet relatively few people with gambling problems seek help. This study examines the extent to which exclusion from casino venues among other factors may act as a motivator for further help-seeking among casino gamblers (both landbased and remote) with at-risk or disordered gambling behavior. In addition, the barriers that prevent gamblers from accepting help are examined. Methods Gamblers from Swiss casinos completed a written questionnaire twice, at 6-month intervals. The questions included whether they had sought help in the past 6 months. Results For those with a SOGS-R rating of 1 or over (n = 173) at the second survey point, a difference in help-seeking was found between the excluded and non-excluded gamblers (p < .001), suggesting that exclusion may be a motivator for help-seeking. Reported differences in levels of debt (p = .006), recognition of gambling problems (p = .010) and severity of gambling-related problems (p = .004) can be taken to suggest that other motivating factors may also influence help-seeking behavior. With regard to the support sought, the most frequently used forms of support were specialized addiction counseling centers (39.5%), followed by self-help groups (21.1%) and remote counseling centers (10.5%). In terms of barriers, reasons relating to attitude, such as denial, appear to pose greater barriers than treatment-related concerns. Discussion From a public health perspective, an overarching strategy is required to increase the share of help-seekers among casino gamblers through targeted measures.